'Look at what we can do with all the broken stuff!' Youth agency and sporting creativity in sites of war, conflict and disaster. Issue 5 (19th October 2016) - Thorpe, Holly
Abstract: Too often youth are considered 'victims' in sites of war, conflict and disaster, with little consideration for their perspectives and ability to develop culturally specific responses to such conditions and events. Thus, unique forms of youth agency, creativity and resourcefulness continue to be overlooked. This paper adopts an interdisciplinary, multi-scale approach to reveal examples of youth agency and sporting creativity within local contexts of conflict and post-disaster, and signals important considerations for Sport for Development and Peace organisations working in such locations. Examining the different scales at which youth are engaging with informal, non-competitive action sports (i.e. skateboarding, parkour) in sites of conflict and disaster, this paper consists of three parts: (1) youth agency in sites of conflict, (2) youth agency in sites of post-disaster, and (3) transnational corporations use of action sports for 'cause marketing' in contexts of 'disaster capitalism'. Each section offers insights from a series of on-going case studies (including interviews, media analysis and digital ethnography) in the post-disaster zones of Christchurch and New Orleans, and conflict zone of Palestine. In so doing, this paper offers a critical examination of the fluid and dynamic nature of youth agency and everyday politics in disrupted and dangerous geographies, but ultimately advocates the need to locate such initiatives within the broader flows of power, which are never neutral, equal or consistent.